2006
DOI: 10.1088/0953-8984/18/38/s09
|View full text |Cite
|
Sign up to set email alerts
|

Numerical treatment of free surface problems in ferrohydrodynamics

Abstract: The numerical treatment of free surface problems in ferrohydrodynamics is considered. Starting from the general model, special attention is paid to field-surface and flow-surface interactions. Since in some situations these feedback interactions can be partly or even fully neglected, simpler models can be derived. The application of such models to the numerical simulation of dissipative systems, rotary shaft seals, equilibrium shapes of ferrofluid drops, and pattern formation in the normal-field instability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
63
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 18 publications
0
63
0
Order By: Relevance
“…The numerical study of a nonlinearly polarizable ferrofluid drop showed similar behaviour to linearly polarizable drops at low magnetic field strengths when drop deformations were not substantial . Lavrova et al (2004Lavrova et al ( , 2006) also considered nonlinearly magnetizable ferrofluid drops and used a finite element method in which the governing equations of the magnetic liquid were coupled by the force balance at the interface and the surface tension was applied as a boundary condition at the interface. Their numerical results of drop equilibrium shapes were in accordance with the theory of Bacri & Salin (1982).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The numerical study of a nonlinearly polarizable ferrofluid drop showed similar behaviour to linearly polarizable drops at low magnetic field strengths when drop deformations were not substantial . Lavrova et al (2004Lavrova et al ( , 2006) also considered nonlinearly magnetizable ferrofluid drops and used a finite element method in which the governing equations of the magnetic liquid were coupled by the force balance at the interface and the surface tension was applied as a boundary condition at the interface. Their numerical results of drop equilibrium shapes were in accordance with the theory of Bacri & Salin (1982).…”
Section: Introductionmentioning
confidence: 99%
“…At sufficiently high fields, shape transitions such as conical tips may occur (Bacri & Salin 1982;Stone, Lister & Brenner 1999;Lavrova et al 2006). Our numerical algorithm to handle such regimes includes modifications to the discretization scheme for the magnetic stress tensor and the averaging scheme for the magnetic fluid properties, within the framework already detailed elsewhere (Afkhami et al 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…The mathematical formulation for hydrodynamics of ferrofluid was discussed by Rosensweig (1985). The deformation of a freely suspended droplet and a sessile droplet in a uniform magnetic field was previously numerically studied by coupling the magnetic field, the free surface, and the fluid flow (Lavrova et al 2006;Sero-Guillaume et al 1992). The stable shape is determined by the interaction between magnetic force and the interfacial tension force.…”
Section: Introductionmentioning
confidence: 99%
“…In every step of the outer iteration the mesh is adapted by Laplace smoothing. The nonlinear magnetization is handled by a fixpoint iteration, see [1], which requires 8 − 10 iterations in this case.…”
Section: Magnetostatic Problemmentioning
confidence: 99%